Effects of microRNA-21 and microRNA-24 inhibitors on neuronal apoptosis in ischemic stroke - Liu, Wansheng (Am J Transl Res, 2016)
Objectives: The purpose of our study was aimed to investigate the effects of microRNA-21 (miR-21) and microRNA-24 (miR-24) inhibitors on ischemic stroke. Methods: MiR-21 inhibitor or miR-24 inhibitor was delivered to Sprague Dawley (SD) rats by continuous intracerebroventricular infusion. Two days later, middle cerebral artery occlusion (MCAO) was performed to induce ischemic stroke. Quantitative real-time PCR was performed to confirm transfection efficiency. The number of apoptotic neurons was detected using TUNEL method. Besides, primary hippocampal or cortical neuronal cultures were prepared from embryonic day 16-18 C57BL/6 mice. These cells were transfected with miR-21 inhibitor, miR-24 inhibitor, or negative scramble RNA. Then the cell viability was detected after transfection, as well as the protein levels of Caspase-3, B-cell lymphoma (Bcl)-xL, and heat shock protein (HSP) 70. Results: Both the levels of miR-21 and miR-24 were significantly reduced by transfection with inhibitors compared to control group or scramble RNA group (both P < 0.05). The apoptosis was significantly reduced in both hippocampal neuron and cortical neuron by miR-24 inhibitor rather than miR-21 inhibitor (P < 0.05), while the cell viability was significantly increased compared to the control group or the scramble group (P < 0.05). In addition, the levels of Bcl-xL and HSP70 were significantly increased, and the levels of Caspase-3 were statistically decreased by transfection with miR-24 inhibitor. Conclusion: MiRNA-24 but not miR-21 inhibitor prevents apoptosis in ischemic stroke by regulation of Bcl-xL, Caspase-3 and HSP70.